Fabrication of a graphene oxide–gold nanorod hybrid material by electrostatic self-assembly for surface-enhanced Raman scattering - Hu, Chaofan; Rong, Jianhua; Cui, Jianghu; Yang, Yunhua; Yang, Lufeng; Wang, Yaling; Liu, Yingliang (Carbon (New York), 2013)
An electrostatic self-assembly procedure was used to fabricate graphene oxide (GO) and gold nanorod (AuNR) hybrids (GO–AuNR), in which poly (N-vinyl-2-pyrrolidone) was used as a stabilizing surfactant to prevent the aggregations of GO sheets. AuNRs were loaded onto the surface of GO, which was confirmed by zeta potential measurements, transmission electron microscopy, atomic force microscopy, UV–Vis–NIR and Raman spectroscopy. The GO–AuNR materials show a great increase of Raman signals for adsorbed aromatic dye molecules, which was demonstrated using cationic and anionic aromatic dyes as probe molecules.